Transient relative age effects across annual age groups in national level australian swimming - Cobley, S.; Abbott, S.; Dogramaci, S.; Kable, A.; Salter, J.; Hintermann, M.; Romann, M. (Journal of Science and Medicine in Sport, 2018)
Objectives: To determine the prevalence, magnitude and transient patterning of Relative Age Effects (RAEs) according to sex and stroke event across all age-groups at the Australian National age swimming Championships. Design: Repeated years of cross-sectional participation data were examined. Methods: Participants were 6014 unique male (3185) and female (2829) swimmers (aged 12-18 years) who participated in Freestyle (50, 400 m) and/or Breaststroke (100, 200 m) at the National age swimming Championships between 2000-2014 (inclusive). RAE prevalence, magnitude and transience were determined using Chi-square tests and Cramer`s V estimates for effect size. Odds Ratios (OR) and 95% Confidence Intervals (CI) examined relative age quartile discrepancies. These steps were applied across age-groups and according to sex and each stroke event. Results: Consistent RAEs with large-medium effect sizes were evident for males at 12-15 years of age respectively, and with large-medium effects for females at 12-14 respectively across all four swimming strokes. RAE magnitude then consistently reduced with age across strokes (e.g., Q1 vs. Q4 OR range 16 year old males = 0.94-1.20; females = 0.68-1.41). With few exceptions, by 15-16 years RAEs had typically dissipated; and by 17-18 years, descriptive and significant inverse RAEs emerged, reflecting overrepresentation of relatively younger swimmers. Conclusions: Performance advantages associated with relative age (and thereby likely growth and maturation) are transient. Greater consideration of transient performance and participation in athlete development systems is necessary. This may include revising the emphasis of sport programmes according to developmental stages and delaying forms of athlete selection to improve validity.